Air drying technique for cytogenetic studies in freshwater planarians (Platyhelminthes) - Margaría, Cecilia Beatriz (1997)
Cytogenetic studies in seawater or land planarians have been generally performed by means of the squash technique (Ball and De Vries 1983; Curini-Galletti et at., 1985, 1989a, b; Martens et at. 1989a, b; Oki et at. 1991; Puccinelli and Curum-Galletti 1987; Tamura et at. 1991). However, the quality of chromosome preparations obtained by squashing in terms of spreading and detritus background is not as good as that obtained by using the air drying technique in other taxa. In addition, few information is available about citogenetic techniques for freshwater invertebrates. The air drying technique (Rothfelds and Siminovitch 1958) was proposed for cytogenetic analysis of mammalian bone marrow cells and it included previous tissue disgregation. For nearly forty years the technique became widely used, with several modifications, for cytogenetic studies even in plant cells. This paper describes the modifications made in the technique for the analysis of planarians chromosomes.